(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of subclinical hypothyroidism in children on Valproic acid monotherapy. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at the Department of Pediatrics, Fauji Foundation Hospital, Rawalpindi, for duration of twelve months from 1st Jan 2018 to 31st Dec 2018. Materials and Methods: Male and female children of age 5 to 12 years, having Idiopathic Epilepsy (IE) and using Valproic Acid Monotherapy (VPA monotherapy) for more than one year, were included in this study. Blood samples were collected from these children and sent to hospital laboratory for thyroid function tests. Subclinical hypothyroidism (SCH) was defined as thyroid stimulating hormone (TSH) levels greater than 5U/ml but less than 10U/ml and free thyroxin (FT4) levels within normal range (5-25ng/ml). The data were analyzed on SPSS 16.0 and the frequency of children having subclinical hypothyroidism was calculated. Results: A total of 122 patients were included in the study. The mean age of the patients was 8.71+1.95 years and the mean duration of treatment with VPA monotherapy was 20.45+5.31 months. The frequency and percentage of male and female patients was 83 (68.0) and 39 (32.0). The frequency and percentage of subclinical hypothyroidism in the study group was found to be 20 (16.4). Conclusion: The frequency of subclinical hypothyroidism is substantial in children using Valproic acid monotherapy for more than one year.